Clinical practice recommendations for use of allogeneic hematopoietic cell transplantation in chronic lymphocytic leukemia on behalf of the Guidelines Committee of the American Society for Blood and Marrow Transplantation - Kharfan-Dabaja, Mohamed A.; Kumar, Ambuj; Hamadani, Mehdi; Stilgenbauer, Stephan; Ghia, Paolo; Anasetti, Claudio; Dreger, Peter; Montserrat, Emili; Perales, Miguel-Angel; Alyea, Edwin P.; Awan, Farrukh T.; Ayala, Ernesto; et al. (Biology of blood and marrow transplantation, 2016)
We sought to establish clinical practice recommendations to redefine the role of allogeneic hematopoietic cell transplantation (allo-HCT) for patients with chronic lymphocytic leukemia (CLL) in an era of highly active targeted therapies. We performed a systematic review to identify prospective randomized controlled trials comparing allo-HCT against novel therapies for treatment of CLL at various disease stages. In the absence of such data, we invited physicians with expertise in allo-HCT and/or CLL to participate in developing these recommendations. We followed the Grading of Recommendations Assessment, Development and Evaluation methodology. For standard-risk CLL we recommend allo-HCT in the absence of response or if there is evidence of disease progression after B cell receptor (BCR) inhibitors. For high-risk CLL an allo-HCT is recommended after failing 2 lines of therapy and showing an objective response to BCR inhibitors or to a clinical trial. It is also recommended for patients who fail to show an objective response or progress after BCR inhibitors and receive BCL-2 inhibitors, regardless of whether an objective response is achieved. For Richter transformation, we recommend allo-HCT upon demonstration of an objective response to anthracycline-based chemotherapy. A reduced-intensity conditioning regimen is recommended whenever indicated. These recommendations highlight the rapidly changing treatment landscape of CLL. Newer therapies have disrupted prior paradigms, and allo-HCT is now relegated to later stages of relapsed or refractory CLL.